Optimizing Integrated Waste Management Planning: A Community-Based Approach to Waste Processing - Sujatmiko, Dedi; Rahim, Robbi; Nurmawati, Nurmawati; GS, Achmad Daengs (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This paper presents a community-based approach to optimize waste management planning in Cangkringsari village, located in Indonesia. The project employed a Participatory Action Research (PAR) methodology, combining academic theory with practical community engagement to design and implement a sustainable waste processing system. The project’s objectives were to create a comprehensive waste management plan, develop community awareness regarding waste segregation, and implement an integrated waste processing system. The approach involved participatory action research (PAR), where local community members collaborated in the planning, design, and execution phases. As a result, the community successfully developed a sustainable waste management plan that addressed local environmental challenges while promoting long-term community involvement. The outcomes of the project indicate significant improvements in waste processing efficiency and community engagement, with a noticeable reduction in environmental pollution. This paper concludes by discussing the implications of the community-based approach for broader waste management practices and provides recommendations for further development and scaling of the project. The project highlights the importance of local involvement in addressing environmental issues and emphasizes the role of service learning in bridging the gap between academic knowledge and real-world solutions